Region i glottodydaktyka. Literacki obraz kultury Górnego Śląska na przykładzie Baru na starym osiedlu Sabiny Waszut .......... 205 - Gęsina, Tomasz (Kultura i literatura w glottodydaktyce polonistycznej wobec wymagań rzeczywistości, 2025)
REGION AND GLOTTODIDACTICS. THE LITERARY IMAGE OF UPPER SILESIAN CULTURE AS EXEMPLIFIED BY SABINA WASZUT’S BAR NA STARYM OSIEDLUKatowice is an academic center where every year students come not only from Poland but also from all over the world. The city is part of Upper Silesia – a region extremely rich in culture, where an important role is played by, among others, cuisine, language, work ethic, attachment to tradition and industrialism, shaping the regional identity of the inhabitants. One of the novels that takes up this topic is Bar na starym osiedlu by Sabina Waszut, which takes place in Chorzów. The book presents the fate of Ola Kieś, a young woman who returns to Upper Silesia after many years and rediscovers its culture. The novel is also a valuable source of knowledge for a foreigner learning Polish, who, as part of the classes, acquires not only knowledge of the language, but also of the culture, especially that which is specific to a given area. Therefore, the article presents the glottodidactic potential of Waszut’s book with particular emphasis on the common, stereotypical knowledge about the culture of Upper Silesia, which a foreigner, especially one studying in the Silesian Voivodeship, should be equipped with in order to gradually begin learning about the complex specificity of this region.